2011
DOI: 10.1186/1475-2840-10-12
|View full text |Cite
|
Sign up to set email alerts
|

Regular physical exercise training assists in preventing type 2 diabetes development: focus on its antioxidant and anti-inflammatory properties

Abstract: Diabetes mellitus has emerged as one of the main alarms to human health in the 21st century. Pronounced changes in the human environment, behavior and lifestyle have accompanied globalization, which resulted in escalating rates of both obesity and diabetes, already described as diabesity. This pandemic causes deterioration of life quality with high socio-economic costs, particularly due to premature morbidity and mortality. To avoid late complications of type 2 diabetes and related costs, primary prevention an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
167
0
11

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(184 citation statements)
references
References 100 publications
6
167
0
11
Order By: Relevance
“…Different studies showed a direct relationship between PVL, obesity and DMT2 [29][30][31][32]. The positive effects of regular aerobic and resistance exercise in DMT2 patients is well established-included improving glycemic control, improving lipid profile indices and decreasing diabetic complications [33][34][35][36][37]. But there are contradictory studies about the effect of exercise on PVL.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies showed a direct relationship between PVL, obesity and DMT2 [29][30][31][32]. The positive effects of regular aerobic and resistance exercise in DMT2 patients is well established-included improving glycemic control, improving lipid profile indices and decreasing diabetic complications [33][34][35][36][37]. But there are contradictory studies about the effect of exercise on PVL.…”
Section: Discussionmentioning
confidence: 99%
“…For example, among adult patients with metabolic syndrome higher levels of systemic inflammation and oxidative stress and lower TAC were demonstrated . A practice of regular exercise in the elderly leads to adaptation to oxidative and nitrosative stresses, decreasing mitochondrial release of free radicals and their reactive species, increasing TAC and cellular antioxidants such as GSH and nitric oxide, which in turn improve endothelial health and reduce systemic inflammation contributing to decreased risk of hypertension, type 2 diabetes, atherosclerosis and metabolic syndrome (Fatouros et al 2004;Maeda et al 2004;Suvorava and Kojda 2007;Seals et al 2009;Gando et al 2010;Newsholme et al 2010;Teixeira-Lemos et al 2011). Thus, regular exercise can afford an excellent maintenance of lower levels of oxidative stress with adequate levels of total antioxidants, promoting healthy aging.…”
Section: Antioxidant Capacity and Healthy Aging: Does Exercise Matter?mentioning
confidence: 99%
“…Taking too much sugary beverages and lemonade can augment the risk of diabetes [9]. Research finding showed that eating a diet of high calorie, beverages, and refined foods significantly increase the risk of T2DM [10]. In the person with obesity, body fat interacts with insulin and other hormones to influence the development of diabetes.…”
Section: Introductionmentioning
confidence: 99%